Prevalence of Asthma, Eczema and Allergic Rhinitis Symptoms in School Children of Kathmandu Valley: Results of a Questionnaire Survey - Sharma, Arun Kumar; Basnet, Sudha; Thapa, Surya B (Journal of Nepal Paediatric Society, 2018)
Introduction: Asthma is the most common chronic disease in children. This study was performed to determine the prevalence of asthma, eczema and allergic rhino-conjunctivitis symptoms in school children of Kathmandu. Methods: This questionnaire-based survey was conducted from December 2009 to August 2010 in 13 schools of Kathmandu among children aged six to seven years and 13 to 14 years based on questions adapted from International Study on Asthma and Allergies in Children (ISAAC) and translated into Nepali. Data were analysed using SPSS and prevalence of self-reported asthma-like symptoms, eczema and allergic rhinitis were assessed. Results: The questionnaire was distributed to 8269 children with a response rate of 68.54%. About 7.5% replied positively for "ever wheezed” (8.1% in older and 6.4% in young children) and 5.2% reported, "current wheeze" (4.2% in younger and 5.8% in older children). Boys had more frequent wheezing than girls in both age groups (p < 0.05). More children had nocturnal cough not associated with cold or chest infection (16.0%) and exercise-induced symptoms (9.4%). The overall prevalence of eczema was 6.2%; younger children (7.2%) reporting symptoms more commonly than older children (5.6%). The reported prevalence of allergic rhinitis was 28.2% (31.2% in older as compared to 22.9% in younger children). Allergic symptoms like “current wheeze”, “eczema” and “allergic rhinitis” were frequently reported together. Conclusion: Asthma, eczema and allergic rhinitis are common in school children of Kathmandu. A multi-centre study across all ecological zones in both rural and urban settings including video questionnaire will more accurately estimate asthma prevalence and its trends in school children of Nepal.